'Real-world' antithrombotic treatment in atrial fibrillation: The EORP-AF pilot survey - Lip, Gregory Y H; Laroche, Cécile; Dan, Gheorghe-Andrei; Santini, Massimo; Kalarus, Zbigniew; Rasmussen, Lars Hvilsted; Ioachim, Popescu Mircea; Tica, Otilia; Boriani, Giuseppe; Cimaglia, Paolo; Diemberger, Igor; Hellum, Camilla Fragtrup; et al. (The American journal of medicine, 2014)
Current guidelines strongly recommend that oral anticoagulation should be offered to patients with atrial fibrillation and ≥1 stroke risk factors. The guidelines also recommend that oral anticoagulation still should be used in the presence of stroke risk factors irrespective of rate or rhythm control. In an analysis from the dataset of the EURObservational Research Programme on Atrial Fibrillation Pilot Survey (n = 3119), we examined antithrombotic therapy prescribing, with particular focus on the risk factors determining oral anticoagulation or antiplatelet therapy use. When oral anticoagulation was used among admitted patients in whom no pharmacologic cardioversion, electrical cardioversion, or catheter ablation was performed or planned, vitamin K antagonist therapy was prescribed in the majority (72.2%), whereas novel oral anticoagulants were used in the minority (7.7%). There was no significant difference in bleeding risk factors among the patients treated with the different types of antithrombotic therapies, except for those with chronic kidney disease, in whom oral anticoagulation was less commonly used (P = .0318). Antiplatelet therapy was more commonly used in patients with a high Hypertension, Abnormal renal/liver function, Stroke, Bleeding history or predisposition, Labile international normalized ratio, Elderly (>65 years), Drugs/alcohol concomitantly score (≥2) (P < .0001). More oral anticoagulation use was associated with female gender (P = .0245). Less novel oral anticoagulant use was associated with valvular heart disease (P < .0001), chronic heart failure (P = .0010), coronary artery disease (P < .0001), and peripheral artery disease (P = .0092). Coronary artery disease was the strongest reason for combination therapy with oral anticoagulation plus antiplatelet drug (odds ratio, 8.54; P < .0001). When the Congestive heart failure, Hypertension, Age ≥75 [Doubled], Diabetes, Stroke [Doubled]-Vascular disease, Age 65-74, and Sex category [female] score was used, 95.6% of patients with a score ≥1 received antithrombotic therapy, with 80.5% of patients with a score ≥1 receiving oral anticoagulation. Of note, 83.7% of those with a score ≥2 received antithrombotic therapy. Of the latter, 70.9% of those with a score ≥2 received oral anticoagulation, vitamin K antagonists were used in 64.1%, and novel oral anticoagulants were used in 6.9%. The EURObservational Research Programme on Atrial Fibrillation Pilot Survey provides contemporary data on oral anticoagulation prescribing by European cardiologists for atrial fibrillation. Although the uptake of oral anticoagulation (mostly vitamin K antagonist therapy) has improved since the Euro Heart Survey a decade ago, antiplatelet therapy is still commonly prescribed, with or without oral anticoagulation, whereas elderly patients are commonly undertreated with oral anticoagulation.